MENURUNKAN KECEMASAN BELAJAR SANTRI BARU MELALUI BIMBINGAN DAN KONSELING - Hudayana, Elif; Jannah, Chaerul; Hartinah, Adha Siti; Subhi, Muhamad Rifa'i (STKIP Muhammadiyah Pringsewu, 2019)
This research intend to describe about anxiety experienced by the new students of Islamic Boarding School Al-Hadi Pekalongan. The scope of this research there are objective anxiety and neurotic anxiety. The method who used inthis research is Qualitative Descriptive and using Miles and Huberman?s data analysis techniques. This research shows that the new student of Islamic Boarding School Al-Hadi Pekalongan have free floating neurotic anxiety. In this case, student revealed that himself often experienced anxiety to something not real. The student get the expectation, however accompanied also with anxiety or can be called anxious. This anxiety is named a free floating neurotic anxiety. The role of guidance and counseling to lowered the anxiety learning of new student is trough cognitive counseling. Cognitive counseling emphasize to counselee belief so that able to change negatif thinking and maladaptif thinking to be positif thinking and adaptif thinking. Trough this positif thinking the anxiety learning student will be come down even disappear.